2019
DOI: 10.1016/j.enbuild.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Case study of the upgrade of an existing office building for low energy consumption and low carbon emissions

Abstract: This case study evaluates the best energy efficiency measures of an existing two-story office building from the late 1960s located in Vancouver. Natural gas was used for heating and electricity was used for lighting, cooling and other needs. The building was simulated to match both metered data and bills. The energy model allowed identifying the parameters to reduce the energy consumption and mitigate the impact on CO2-eq emissions. On-site renewable energy supply was simulated. The return on investment (ROI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 36 publications
(51 reference statements)
1
26
0
Order By: Relevance
“…They include thermal insulation of the building envelope and replacement or use of window and door frames with a lower heat transfer coefficient as well as elimination of cold bridges. Energies 2020, 13,1968 4 of 20…”
Section: Methods To Improve Energy Efficiency and Reduce Demand In Bumentioning
confidence: 99%
See 4 more Smart Citations
“…They include thermal insulation of the building envelope and replacement or use of window and door frames with a lower heat transfer coefficient as well as elimination of cold bridges. Energies 2020, 13,1968 4 of 20…”
Section: Methods To Improve Energy Efficiency and Reduce Demand In Bumentioning
confidence: 99%
“…The highest heat energy loss in a building is related to the ventilation system and heat exchange through dividing structures and windows and door frames. In a paper by Charles et al [13], the authors analyzed the improvement in energy performance of an existing two-story office building built in the late 1960s located in Vancouver, which involved replacing window frames, insulating external dividing structures (walls and roof), and installing renewable energy on an office building. The results showed that the improvement made on the building envelope allowed the reduction of 45% of the annual energy consumption.…”
Section: Methods To Improve Energy Efficiency and Reduce Demand In Bumentioning
confidence: 99%
See 3 more Smart Citations